ANALISIS PEMASARAN SUSU SEGAR SAPI PERAH DI KECAMATAN MOJOSONGO KABUPATEN BOYOLALI, JAWA TENGAH - Sutrisno Hadi Purnomo; Ayu Intan Sari; Muhammad Abdul Haris (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
This study aims to determine the most efficient marketing channel based on what collectors pass through to distribute fresh milk and maintain the quality of fresh milk by choosing the closest route, the fastest time and cost efficiency. In addition, this study aims to determine marketing costs, marketing margins, profits and marketing efficiency carried out by marketing agencies involved in the fresh milk marketing system. This research was conducted in Mojosongo District, Boyolali Regency, Central Java. This research was conducted in Mojosongo District, Boyolali Regency, Central Java. The basic method of this research is descriptive method and its implementation uses a survey method. The research location was taken purposively based on the consideration that Mojosongo District has the second largest dairy cow population in Boyolali Regency. The analysis method used is the analysis of marketing costs, marketing margins, marketing profits, marketing efficiency and the Traveling Salesman Problem analysis to determine the closest distance, fastest time and lowest cost. There are three channels for the Marketing of Fresh Milk for Dairy Cows used by producers in Mojosongo District as follows: Channel I: Farmers to Consumers, Channel II: Farmers to Traders, Collectors to Consumers and Channel III: Farmers to Traders, collectors to Wholesalers to the milk processing industry Channel I is the most efficient marketing channel because in this channel breeders sell directly to consumers. The most efficient marketing channel using the Traveling Salesman Problem method is distribution line II because this route has the closest distance, the fastest time to maintain the quality of fresh milk and cost efficiency.